Estimation of salt intake and sodium-to-potassium ratios assessed by urinary excretion among Japanese elementary school children. (4th July 2018) - Seko, Chikako; Taguchi, Yuko; Segawa, Hiroyoshi; Odani, Kiyoko; Aoi, Wataru; Wada, Sayori; Kitaoka, Kaori; Masumoto, Taeko; Higashi, Akane
ABSTRACT: Dietary salt intake is largely responsible for the increase in blood pressure with age. It is important to start effective prevention approaches during childhood. In this study, we estimated salt intake and sodium-to-potassium (Na/K) ratios assessed by urinary excretion among elementary school children in Kyoto, Japan. A total of 331 subjects aged 9–11 years participated in school checkups in April 2015. Urinary concentrations of sodium, potassium, and creatinine were measured in first morning urine samples. The subjects' dietary habits were confirmed by questionnaires completed by their parents. The median estimated urinary sodium excretion was 129.0 mmol/day (5.7g/day of salt). In 30.2% of the subjects, their estimated salt intake exceeded their age-specific dietary goal for salt intake recommended by the Dietary Reference Intakes for Japanese 2015. Multivariate linear regression model analysis after adjustment for age revealed a significant positive correlation between seaweeds or fish paste products consumption and the estimated salt intake ( p  = 0.02 and 0.02, respectively). The median urinary Na/K ratio (mEq/mEq) was 4.5. Multivariate linear regression model analysis revealed a significant negative correlation between fruit consumption and urinary Na/K ratio ( p  = 0.04). These results suggest that the high sodium intake and the high Na/K ratios occur among Japanese elementary school children, and that the urinary Na/K ratio in children may be reduced by the daily consumption of fruit.